Experiential marketing as a predictor of repurchase intentions of Smartphones amongst youth in South Africa - Sebopa, Caroline Boitumelo (My University, 2017)
Globally there has been a decrease in fixed line telephones while Smartphone sales have been on the rise; the same trend has also been happening in South Africa. Due to this trend, Smartphone brands have been placing importance on the retention of existing customers, therefore focusing on repurchase intentions. The research investigates the relationship between experiential marketing (sense, feel, think, act and relate experience), customer satisfaction and the repurchase intentions of Smartphones amongst the youth market of South Africa. The paper reviews literature on experiential marketing, customer satisfaction and repurchase intentions, then tests six hypotheses which were proposed which led to the development of a research model. Non-probability sampling was used at The University of the Witwatersrand where the study was conducted amongst 223 youth aged 15 – 35 years. Structural equational modelling was used to analyse the data, using SPSS and Amos software. The results revealed sense experience has the most influence on the customer satisfaction of Smartphone brands which then leads to repurchase intentions. The findings are expected to add to literature on experiential marketing, customer satisfaction and repurchase intentions as well as provide practical implications.
A research report submitted to the faculty of commerce, law and management, university of the Witwatersrand, in partial fulfilment of the requirements for the degree of master of management in Strategic Marketing.
Keywords: Consumer satisfaction--South Africa; Consumer's preferences--South Africa; Marketing--South Africa; Smartphones--South Africa